Complex evolutionary trajectories of sex chromosomes across bird taxa - Zhou, Q.; Zhang, J.; Bachtrog, D.; An, N.; Huang, Q.; Jarvis, E.; Gilbert, Thomas; Zhang, G. (The American Association for the Advancement of Science, 2014)
Sex-specific chromosomes, like the W of most female birds and the Y of male mammals, usually have lost most genes owing to a lack of recombination. We analyze newly available genomes of 17 bird species representing the avian phylogenetic range, and find that more than half of them do not have as fully degenerated W chromosomes as that of chicken. We show that avian sex chromosomes harbor tremendous diversity among species in their composition of pseudoautosomal regions and degree of Z/W differentiation. Punctuated events of shared or lineage-specific recombination suppression have produced a gradient of “evolutionary strata” along the Z chromosome, which initiates from the putative avian sex-determining gene DMRT1 and ends at the pseudoautosomal region. W-linked genes are subject to ongoing functional decay after recombination was suppressed, and the tempo of degeneration slows down in older strata. Overall, we unveil a complex history of avian sex chromosome evolution.